Visualized trends and bibliometric analysis in ankle cartilage repair from 2004 to 2024 - Fu, Xuefei; Zhang, Zhixing; Wang, Yingxiang; Lu, Lin; Chen, Tao; Deng, Haobin; Li, Hao; Yu, Defu (Frontiers in Medicine, 2024)
Ankle cartilage injuries are a common sports-related condition that significantly impairs patients’ daily activities and imposes substantial economic burdens on both families and society. Effective cartilage repair strategies are crucial to addressing this pathological condition. Current conservative treatments include muscle strengthening, use of ankle braces, physical therapy, and the administration of NSAIDs. In cases of severe injury, surgical interventions such as osteophyte resection and cartilage transplantation may be necessary. However, the inherent regenerative capacity of articular cartilage is limited, and conventional treatments are insufficient to promote cartilage regeneration and repair. Consequently, innovative therapies such as stem cell therapy, exosome therapy, and cartilage regeneration scaffolds are prioritized for future development. In recent years, significant progress has been made in ankle cartilage repair. While bibliometric studies on cartilage repair exist, specific analyses focused on ankle cartilage repair are lacking. This study aims to address this gap by conducting a bibliometric analysis of 131 articles published over the past two decades, highlighting development trajectories, research hotspots, and evolutionary trends through knowledge mapping. Our findings indicate growing global interest, with the United States leading in international collaboration, funding, publication output, and citation frequency. Foot & Ankle International emerges as the leading journal for publication and dissemination in this field, with Kerkhoffs GMMJ identified as the most influential author. Notable hotspot keywords include “osteochondral lesions” and “platelet-rich plasma.” By highlighting critical research hotspots and collaboration patterns, this study not only enriches the existing literature on ankle cartilage repair but also serves as a foundational resource for clinicians and researchers aiming to develop innovative strategies for improving patient outcomes. Furthermore, our findings underscore the necessity of interdisciplinary collaboration in advancing the understanding and treatment of ankle cartilage injuries. Ultimately, the visual characterization of these trends provides valuable insights into the field’s evolutionary trajectory, offering guidelines for future research directions and encouraging further exploration of this promising area.